The manuscripts of Mícheál Óg that were sold to Sir William Betham - Sharpe, R (Cló Torna, 2018)
Sir William Betham bought a high proportion of his Irish manuscripts from Peadar Ó Longáin and his brother Pól, but the extent of the collection and its reliance on the Carrignavar scribes has not been noticed. It is shown here that Betham was not like their other clients, who bought newly made copies of a repertoire of well-known texts. He bought older manuscripts, including some of their exemplars, but he was induced also to take twenty-two volumes of their father Mícheál Óg’s papers, arranged into volumes for sale and bound on receipt by Betham. Some of John Windele’s correspondence shows that Betham bought what is now RIA MS 23 N 10 from Pól Ó Longáin, who got it from Seán Ó Loimeasna and kept it by deceit. The correspondence, Betham's bindings, and the assignment of roman numerals to volumes in the collection provide some means to date Betham’s purchases between c. 1839 and 1846. He bought books owned by the brothers or for which they acted as middlemen, but it also appears that anything they had was for sale, including the manuscript held in their father’s hands on the day of his death.